Effect of spirulina enriched Artemia on the body composition of red tilapia (Oreochromis sp.) - Abd. Jalil, Mohd. Izwannizar (2013)
The effect of Spirulina enriched Artemia on the proximate analysis of red tilapia (Oreochromis niloticus.) tissue was investigated. The experiment was conducted in 15 days that involved 3 locations which were the Institute of Bioscience, Nutrition Study Laboratory (Department of Aquaculture, Faculty of Agriculture, University Putra Malaysia) and Nutrition Study Sector, MARDI. The red tilapia, aged about 2 weeks were stocked into 12 tanks. Each tank contained 11L of freshwater and 110 tilapia individuals. There were 4 different treatments tested with 3 replicates for each treatment. Each 3 tanks were given treatment T1 (unenriched Artemia) , T2 (Artemia enriched with Spirulina for 3 hours), T3 (Artemia enriched with Spirulina for 6 hours) and T4 (Artemia enriched with Spirulina for 9 hours). All the diets tested were frozen before given to the fish 3 times per day. Initial proximate analysis was done before the culture period begins. After 15 days, the proximate analysis was once again done as final results. Water quality parameters were also measured throughout the culture period. Water quality parameters that have been measured were pH, dissolved oxygen (DO), water temperature and ammonia-nitrogen content. Result showed that unenriched and enriched Artemia gave effect on proximate analysis of the red tilapia. Treatment T4 (Artemia enriched with Spirulina for 9 hours) is the best compared to other treatments.